2014
DOI: 10.3329/jbs.v20i0.17735
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding and fertilization on the growth and production of puntius sophore in seasonal ponds in Natore, Bangladesh

Abstract: Context: Local farmers believe that the seasonal ponds and ditches which can retain water for 4 to 6 months in a year cannot be utilized for fish production but in fact such waters hold tremendous potential for culture of small indigenous fish species.Objectives: To evaluate the effects of fertilization and feeding in the growth and production of Puntius sophore culture in seasonal ponds. Materials and Methods:Six ponds were used during this study under two treatments. Two treatments such as T1 (only fertilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…According to Swingle (1967) and , pH 6.5 to 9.0 is suitable for pond fish culture and pH more than 9.5 is unsuitable because free CO 2 is not available in this situation. Kamal et al (2012) found the pH values ranged from 6.88 to 9.22 at the seasonal ponds of Natore, Bangladesh. Fortnightly fluctuations of total alkalinity in the experimental ponds ranged from 128.00 to 188.00 mg/l.…”
Section: Physical Parameters and Chemical Parametersmentioning
confidence: 99%
See 3 more Smart Citations
“…According to Swingle (1967) and , pH 6.5 to 9.0 is suitable for pond fish culture and pH more than 9.5 is unsuitable because free CO 2 is not available in this situation. Kamal et al (2012) found the pH values ranged from 6.88 to 9.22 at the seasonal ponds of Natore, Bangladesh. Fortnightly fluctuations of total alkalinity in the experimental ponds ranged from 128.00 to 188.00 mg/l.…”
Section: Physical Parameters and Chemical Parametersmentioning
confidence: 99%
“…Hossain (2012) found the DO content ranged from 4.8-8.7 ppm. Kamal et al (2012) recorded DO content varried from 1.80 mg/l to 9.8 mg/l in the seasonal ponds of Natore, Bangladesh. Banerjea (1967) stated that 5-7 ppm of dissolved oxygen of a water body is good for biological productivity.…”
Section: Physical Parameters and Chemical Parametersmentioning
confidence: 99%
See 2 more Smart Citations